Harnessing digital innovations for climate action and market access: Opportunities and constraints in the CWANA region - Tabe-Ojong, Martin Paul; Salama, Yousra; Abay, Kibrom A.; Abdelaziz, Fatma; Zaccari, Claudia; Akramkhanov, Akmal; Menza, Gianpiero; Anarbekov, Oyture (Elsevier, 2024)
There is growing optimism about the potential of digital innovations to support climate action and transform agricultural markets. We review and characterize the landscape of digital innovations in the Central and West Asia and North Africa (CWANA) region. We highlight major success stories associated with the potential of digital innovations to facilitate rural market transformation and support climate action, including adaptation and mitigation. Our desk and landscape review identifies various digital innovations used in Egypt, Morocco, and Uzbekistan. We then create a typology of digital innovations based on seven broad service categorizations: weather and climate; agricultural finance; energy and early warning systems; data and crowdsourcing; market information and market place; extension and advisory information; and supply chain coordination. Three technical and validation workshops supplement this review. Our review shows that digital innovations have the potential to build resilience to climate change and increase market access, but their adoption remains low and varying across contexts. Significant heterogeneity and differences exist across these countries, possibly due to different institutional and regulatory frameworks that guide demand and capacity. We identify several supply and demand-side constraints facing the digital ecosystem in the region. There is the existence of a significant digital divide fueled by gender, literacy gaps, and related socioeconomic and psychosocial constraints. A seeming disconnect also exists between pilots and scale-ups, as most existing digital applications are unsuccessful in expanding beyond the pilot phase.